Merdeka Bermain, Merdeka Belajar: Sosialisasi Loose Parts Sebagai Metode Paud Masa Kini - Fatimah Noor Isnaini; Octavian Dwi Tanto; Wening Sekar Kusuma (Jurnal Medika: Medika, 2025)
The use of loose parts as a learning medium has emerged as an innovative approach in early childhood education, especially in contexts with limited access to conventional learning tools. Loose parts are natural or recycled objects readily found in children’s environments that can be creatively used to stimulate imagination, critical thinking, and cognitive development. However, field surveys in Ngawi revealed that most early childhood educatiors are not yet implementing loose parts in their teaching, despite having prior knowledge of of the concept. This community service program involved 24 early childhood educators from various regions in Ngawi and was conducted online through lectures, workshops, and evaluating using pre-tests and post-test. The results showed a significant increase in teacher’s understanding and awareness regarding the importance and practical use of loose parts in learning. Post-program feedback indicated that the participants were more confident and motivated to utilize surrounding materials in meaningful learning activities. This initiative is expected to inspire more creative and effective teaching practices in early childhood education.